Structural vector autoregressive analysis - Kilian, Lutz; Lütkepohl, Helmut 1951- (Cambridge University Press, 2017)
Structural vector autoregressive (VAR) models are important tools for empirical work in macroeconomics, finance, and related fields. This book not only reviews the many alternative structural VAR approaches discussed in the literature, but also highlights their pros and cons in practice. It provides guidance to empirical researchers as to the most appropriate modeling choices, methods of estimating, and evaluating structural VAR models. The book traces the evolution of the structural VAR methodology and contrasts it with other common methodologies, including dynamic stochastic general equilibrium (DSGE) models. It is intended as a bridge between the often quite technical econometric literature on structural VAR modeling and the needs of empirical researchers. The focus is not on providing the most rigorous theoretical arguments, but on enhancing the reader's understanding of the methods in question and their assumptions. Empirical examples are provided for illustration
Keywords: Econometric models; Autoregression (Statistics); Regression analysis; Monetary policy -- Econometric models; Regressionsanalyse; Strukturelles vektor-autoregressives Modell; Makroökonomie; Lehrbuch